ABCB1 and ABCG2 Together Limit the Distribution of ABCB1/ABCG2 Substrates to the Human Retina and the ABCG2 Single Nucleotide Polymorphism Q141K (c.421C> A) May Lead to Increased Drug Exposure - El Biali, Myriam; Karch, Rudolf; Philippe, Cécile; Haslacher, Helmuth; Tournier, Nicolas; Hacker, Marcus; Zeitlinger, Markus; Schmidl, Doreen; Langer, Oliver; Bauer, Martin (Frontiers in Pharmacology, 2021)
The widely expressed and poly-specific ABC transporters breast cancer resistance protein (ABCG2) and P-glycoprotein (ABCB1) are co-localized at the blood-brain barrier (BBB) and have shown to limit the brain distribution of several clinically used ABCB1/ABCG2 substrate drugs. It is currently not known to which extent these transporters, which are also expressed at the blood-retinal barrier (BRB), may limit drug distribution to the human eye and whether the ABCG2 reduced-function single-nucleotide polymorphism (SNP) Q141K (c.421C>A) has an impact on retinal drug distribution. Ten healthy male volunteers (five subjects with the c.421CC and c.421CA genotype, respectively) underwent two consecutive positron emission tomography (PET) scans after intravenous injection of the model ABCB1/ABCG2 substrate [11C]tariquidar. The second PET scan was performed with concurrent intravenous infusion of unlabelled tariquidar to inhibit ABCB1 in order to specifically reveal ABCG2 function. In response to ABCB1 inhibition with unlabelled tariquidar, ABCG2 c.421C>A genotype carriers showed significant increases (as compared to the baseline scan) in retinal radiotracer influx K1 (+62 ± 57%, p = 0.043) and volume of distribution VT (+86 ± 131%, p = 0.043), but no significant changes were observed in subjects with the c.421C>C genotype. Our results provide the first evidence that ABCB1 and ABCG2 may together limit the distribution of systemically administered ABCB1/ABCG2 substrate drugs to the human retina. Functional redundancy between ABCB1 and ABCG2 appears to be compromised in carriers of the c.421C>A SNP who may therefore be more susceptible to transporter-mediated drug-drug interactions at the BRB than non-carriers.